Three obstetric factors should be considered in umbilical cord blood donor selection - Škorić, Dejan; Milovanović, Ivan; Dimić, Jovana; Bogićević, Dragana (Vojnosanitetski pregled, 2021)
Background/Aim. The umbilical cord blood (UCB) volume and hematopoietic stem cells count are used as indicators for hematopoietic potential of UBC units. These indicators are affected by a collection method and obstetric factors. It was established that birth weight and placental weight affect the volume and hematopoietic stem cells count in UCB units. The influence of other obstetric factors is less clear. The aim of this study was to investigate the impact of obstetric factors on hematopoietic potential of UCB units. Methods. The study involved 103 consecutive UCB units collected during 2013. Relationship of UCB volume, total nucleated cells, CD34+ cells and Colony Forming Unit-Granulocyte Monocyte count with maternal and neonatal characteristics was retrospectively analyzed. Results. It was shown that birth weight, placental weight and umbilical cord length ≥ 31 cm significantly increased the volume of collected samples, total nucleated cells, CD34+ cells and Colony Forming Unit-Granulocyte Monocyte count. Gestational age between 38−40 weeks increased significantly all umbilical factors (volume, total nucleated cells, CD34+ cells, and Colony Forming Unit-Granulocyte Monocyte count). Gender did not have an influence on quality of UCB units except on total nucleated cells and CD34+ cells count. Other obstetric factors did not affect significantly the quality of UCB units. Conclusion. Our study confirmed that birth weight, placenta weight, length of the umbilical cord and gestational age independently influenced the UCB unit volume, and absolute count of nuclear cells and hematopoietic stem cells. Due to a positive correlation between birth weight and placental weight, only birth weight, umbilical cord length and gestational age should be standard parameters in procedure of donor selection.
Keywords: fetal blood; hematopoiesis; stem cells; obstetrics; granulocyte-macrophage progenitor cells